2013
DOI: 10.1603/ec12162
|View full text |Cite
|
Sign up to set email alerts
|

Do Weaver Ant (Hymenoptera: Formicidae) Marks Affect Mango Internal Quality and Storage Life?

Abstract: In implementing the integrated pest management mango (Mangifera indica L.) program using weaver ants (Oecophylla smaragdina F.) as a major component in the Northern Territory of Australia, we received a number of questions from farmers and extension officers asking whether weaver ant marks reduce internal fruit quality and induce fruit rot, which is economically important. However, this issue has not been investigated. Soluble sugar content in fruits with and without weaver ant marks and observations on the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
2
13
0
2
Order By: Relevance
“…Statistically significant protection was only found when pathogen incidence was high in one out of three years. The mechanism was not investigated, but chemical deposits from the ants were suggested and later supported when Peng and Christian (2013) found that black marks originating from formic acid deposited by weaver ants eliminated fruit rot on mangos. Fruits without marks developed considerable numbers of dark open lenticels, most of which developed patches of rot during 10-day storage.…”
Section: Ant-plant Systems With Pathogen Protectionmentioning
confidence: 99%
“…Statistically significant protection was only found when pathogen incidence was high in one out of three years. The mechanism was not investigated, but chemical deposits from the ants were suggested and later supported when Peng and Christian (2013) found that black marks originating from formic acid deposited by weaver ants eliminated fruit rot on mangos. Fruits without marks developed considerable numbers of dark open lenticels, most of which developed patches of rot during 10-day storage.…”
Section: Ant-plant Systems With Pathogen Protectionmentioning
confidence: 99%
“…Finally, an increased prey turnover may lead to a higher production of ant manure, which has been hypothesized to benefit plant growth and fruit quality (Barzman et al. ; Peng and Christian ).…”
Section: Discussionmentioning
confidence: 99%
“…Providing young colonies with insect traps may shorten their time to reach a size where they can be utilized commercially. Finally, an increased prey turnover may lead to a higher production of ant manure, which has been hypothesized to benefit plant growth and fruit quality (Barzman et al 1996;Peng and Christian 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The colonies can grow to a considerable size, consisting of more than a hundred nests, spanning numerous trees, and a single colony may contain hundreds of thousands of workers (Pinkalski and others 2015). O. smaragdina worker ants produce ant manure droplets from rectal sac fluids and deposit them throughout their territory (Beugnon and Dejean 1992;Dejean and Beugnon 1991;Offenberg and others 2004;Offenberg 2007;Peng and Christian 2013). These droplets contain various nutritious compounds such as amino acids and urea (Vidkjaer and others 2015a;Vidkjaer and others 2015b, unpublished data), which is commonly used as a foliar fertilizer in agriculture (Abad and others 2004;Readman and others 2002;Varga and Svecnjak 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As nitrogen is a limiting factor for plant growth in most ecosystems, (Johnson and Turner 2014;LeBauer and Treseder 2008), O. smaragdina may thus serve as conduits of nutrients for plant growth. Accordingly, it has been hypothesized that the presence of O. smaragdina in orchards enhances the fruit quality due to a fertilizing effect of the ant manure (Barzman and others 1996;Peng and Christian 2013).…”
Section: Introductionmentioning
confidence: 99%